Influence of Na2S on the corrosion behavior of Q345 steel in sodium aluminate solution. (4th September 2019) - Fu, Hui; Chen, Chao-yi; Li, Jun-qi; Lan, Yuan-pei; Wang, Lin-zhu; Yuan, Jing-jiu
Abstract: The influence of S 2− concentration in sodium aluminate solution on the corrosion behavior of Q345 steel was investigated by spray corrosion and electrochemical corrosion tests. Corrosion results showed that the corrosion weight loss and maximum pitting depth of Q345 steel increased as the S 2− concentration increased. Potentiodynamic polarization analysis and electrochemical impedance spectroscopy results indicated that the corrosion current density of Q345 steel increased, whereas the polarization resistance ( R p ) tended to decrease as the S 2− concentration increased. All the characterizations revealed that the corrosion was accelerated with the increase of S 2− concentration. The corrosion products were studied by energy dispersive spectroscopy and x-ray photoelectron spectroscopy. Results indicated that the corrosion products mainly comprised FeO, FeS, and FeOOH. The corrosion mechanism of Q345 steel in sodium aluminate solution with various S 2− concentrations was revealed on the basis of the corrosion behavior and composition of corrosion products.